Beyond the Skin: Holistic Healing of Acne Vulgaris with Homeopathy : A Case Study (Homoeopathy for All, 2025)
Acne vulgaris, a chronic  inflammatory skin condition, was  effectively managed in a 19-year-old  male using individualized classical  homeopathy. Silicea 200C, selected  through totality of symptoms, led to  significant improvement within two  months—reducing inflammation,  preventing new eruptions, and  enhancing skin and emotional  health—highlighting homeopathy’s  constitutional and holistic benefits
Keywords: Acne Vulgaris; Case Study; Constitutional Remedy; Holistic Medicine; Skin Disorders